Assistance for Reproductive Health Workers in Efforts to Increase Pap Smear Coverage - Brahmana, Ivanna Beru; Rosa, Elsye Maria; Sari, Devi Permata; Larasati, Raden Rara Pandhan Budi (Universitas Aisyah Pringsewu, 2025)
Background: Pap smears are essential for the early detection and prevention of cervical cancer, yet the coverage of these screenings in Indonesia is still low, at approximately 7.3%. Health centers are available in nearly all sub-districts, with many areas having additional supporting centers. Health workers in these facilities have been trained on the significance of Pap smear. It is expected that with more active involvement from health workers in educating and assisting local communities, the coverage of Pap smears will improve. Objective: To assess how much Pap smear coverage can increase with effective support from health workers. Method: A descriptive cross-sectional study was conducted with 33 married women in Central Java between July and September 2024, using consecutive sampling. Results: The average age of participants was 43.06 years, and 60.6% (20/33) had never had a Pap smear. Following educational support from health workers, 75.8% (25/33) of participants gained a better understanding of the importance of Pap smear and underwent the screening through the health insurance system in Indonesia called Badan Penyelenggara Jaminan Sosial (BPJS) at a designated laboratory. Conclusion: Health worker support led to a significant increase in Pap smear coverage, reaching 75.8%.